Pengaruh Kualitas Pelayanan terhadap Kepuasan Masyarakat pada Program Administrasi Terpadu Kecamatan (PATEN) di Kantor Kecamatan Kayu Aro Barat Kabupaten Kerinci - Oktaviani, Hafisah; Syamsir, Syamsir (PUBLICNESS: Journal of Public Administration Studies, 2023)
The goal of this study was to determine the level of community satisfaction with the District Integrated Administration Program (PATEN) at the Kerinci Regency's Kayu Aro Barat District office. The responsiveness of employees in providing services to the community is one of the major issues contributing to community unhappiness. The Kayu Aro Barat District Office must therefore preserve the confidence and satisfaction of the general public by raising the standard of its services. Multiple linear regression and a quantitative approach were used in this study. Strategies for gathering data via questionnaires. 86 participants participated in this survey as respondents. The Random Sampling method is employed in the sampling process. The IBM Statistical Package for Social Science (SPSS) version 20.0 application was used to calculate the hypothesis testing. The District Integrated Administration Program is not significantly impacted by responsiveness, but it is impacted by reliability, physical ability, assurance, and empathy.